Penerapan Konsep Monitoring Dan Evaluasi Dalam Sistem Informasi Kegiatan Mahasiswa Di Perbanas Institute Jakarta - Dhia Farida Ariefni; Mercurius Broto Legowo (Jurnal Teknik Informatika dan Sistem Informasi, 2018)
The purpose of this research is to apply the monitoring & evaluation concept (M & E) in the student activity information system in the study program at Perbanas Institute. Student activities in higher education are usually very numerous and varied and require a financial aspect. Lack of monitoring and evaluation is the main problem faced by the study program on student activities. Thus, the M & E concept (including inputs, activities, outputs, outcomes, and impacts) needs to be applied to address these issues. The results of this study present Monitoring and Evaluation Information Systems for student activities in Study Program. This M & E information system for student activities will contribute to supporting the performance of the study program.